Challenges and Improvements of Novel Therapies for Ischemic Stroke - Yang, Lijun; Qian, Jing; Yang, Bo; He, Qiaojun; Wang, Jiajia; Weng, Qinjie (Frontiers in Pharmacology, 2021)
Stroke is the third most common disease over the world, which is regarded as a hotspot in medical research because of its high mortality and morbidity. Stroke, especially ischemic stroke, causes severe neural cell death and no effective therapy currently is available for neuroregeneration after stroke. Although many therapies have been shown effective in preclinical studies of ischemic stroke, almost none of them passed clinical trials and the reasons for most failures have not been well identified. In this review, we focus on several novel methods like Traditional Chinese Medicine, stem cell therapy as well as exosomes that haven’t been used for ischemic stroke till recent decades. We summarize the proposed basic mechanisms underlying these therapies and related clinical results, discussing advantages and current limitations for each therapy emphatically. Based on the limitations like side effects, narrow therapeutic window and less accumulation at the injury region, structure transformation and drug combination are subsequently applied, providing a deep understanding to develop effective treatment strategies for ischemic stroke in the near future.